Rare earth modified oxide catalyst taking copper-aluminum hydrotalcite as precursor as well as preparation method and application of rare earth modified oxide catalyst
Through the copper-aluminum hydrotalcite catalyst modified by rare earth elements, the Sm2O3-coated copper nanoparticle structure is formed, which solves the problems of low temperature activity and poor stability of copper-based catalysts in methanol steam reforming reaction, and significantly improves the activity and stability of the catalyst and the repeatable regeneration of the catalyst is achieved.
Patent Information
- Application Number
- CN202411477667.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing copper-based catalysts have low low temperature activity and poor stability in methanol steam reforming reactions, which limits their application in MSR reactions.
Copper-aluminum hydrotalcite modified with rare earth elements is used as the precursor, and the rare earth element is anchored on the copper-aluminum hydrotalcite layer by double drop method, and after roasting, the rare earth-modified copper-aluminum oxide catalyst is obtained to form Sm2O3 coating The structure of copper nanoparticles improves the activity and stability of the catalyst.
The low-temperature activity and stability of the catalyst have been significantly improved. The CH3OH conversion rate of the copper-aluminum oxide catalyst can reach 84.8% at 250℃, and the hydrogen production rate can reach 594.9 mmol/gcat/h, and it remains good in multiple cycle tests. Regeneration ability.
Smart Images

Figure HDA0005096540830000011 
Figure HDA0005096540830000012 
Figure HDA0005096540830000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic material preparation, and specifically relates to a rare earth modified oxide catalyst using copper-aluminum hydrotalcite as a precursor, and a preparation method and application thereof. Background Art
[0002] Hydrogen (H 2 ) is known as the "fuel of the future". It has been intensively developed and studied in the past two decades due to its high mass energy density and the fact that its combustion products only produce water that is harmless to the environment. Hydrogen can be derived from clean energy such as solar energy, wind energy, and geothermal energy. Therefore, clean "green hydrogen" is one of the powerful solutions to the current energy problem. However, due to the wide range of hydrogen explosion limits, the transportation and storage of hydrogen is still the biggest obstacle to the hydrogen economy. Methanol (CH 3 OH) is a small molecule with a high hydrogen-to-carbon ratio and is known as clean "coal", cheap "oil", simple "gas", mobile "electricity", and liquid "hydrogen". Methanol is also an easily available biofuel. The methanol steam reforming (MSR) reaction converts CH 3 OH and H 2 O to H 2 and CO 2 , the methanol steam reforming process has developed to a relatively mature stage, and Sinopec Group has built China's first methanol hydrogen production and hydrogenation integrated station in 2023. Using the MSR reaction for in-situ hydrogen production of hydrogen energy vehicles or coupling proton exchange membrane fuel cells for new energy vehicles is an important part of the current "hydrogen economy". In order to apply MSR to actual small-scale mobile hydrogen production devices, researchers are committed to the development of low-temperature catalysts for MSR reactions, among which precious metal-based catalysts and copper-based catalysts are more deeply studied. Precious metal-based catalysts are limited in their large-scale application due to their high cost and limited reserves, while copper-based catalysts represented by commercial copper-zinc-aluminum still have two main problems: low low-temperature activity and poor stability and easy agglomeration. The main direction of current research on copper-based catalysts is to construct a more reactive reaction interface or site while improving the stability of copper-based catalysts in the MSR reaction.
[0003] Layered composite metal hydroxides, also known as hydrotalcites, have microscopic controllability of the chemical composition of the layers and mesoscopic controllability of the grain size and its distribution. The metals in the hydrotalcite layers are evenly dispersed, so after calcination and reduction, evenly dispersed metal catalysts can be obtained. However, oxide catalysts with hydrotalcite as precursors still lack excellent low-temperature activity and good stability in the MSR reaction. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an oxide catalyst using rare earth element modified copper aluminum hydrotalcite as a precursor and its application in methanol reforming reaction. In the method, rare earth elements are simply introduced into the preparation process to anchor them on the copper aluminum hydrotalcite layer. The obtained rare earth modified catalyst has better MSR reaction activity and better stability than the unmodified copper aluminum catalyst. It is found that the rare earth modified copper aluminum oxide catalyst forms Sm due to the strong interaction between the metal carrier and the catalyst in the methanol steam reforming reaction. 2 O 3 The structure of the coated copper nanoparticles has established a simple regeneration method for rare earth modified copper aluminum oxide catalysts, providing innovative ideas and solutions to solve the current problems of low low-temperature activity and poor stability of copper-based catalysts.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing rare earth modified oxide using copper-aluminum hydrotalcite as a precursor, comprising the following steps:
[0007] (1) Al(NO 3 ) 3 9H 2 O and Cu(NO 3 ) 2 ·3H 2 O mixed solution and NaOH solution were added simultaneously under constant pH conditions using the double drop method. 2 CO 3 The solution is stirred for a period of time to obtain a copper-aluminum hydrotalcite suspension;
[0008] (2) adding a rare earth nitrate solution to the copper-aluminum hydrotalcite suspension obtained in step (1), and simultaneously adding a NaOH solution using a double-drop method to maintain a constant pH, and performing water bath aging to anchor the rare earth hydroxide on the copper-aluminum hydrotalcite layer to obtain a rare earth-modified copper-aluminum hydrotalcite;
[0009] (3) calcining the rare earth-modified copper-aluminum hydrotalcite prepared in step (2) in air to finally obtain a rare earth-modified copper-aluminum oxide catalyst.
[0010] Further, in step (1), the Al(NO 3 ) 3 9H 2 O and Cu(NO 3 ) 2 ·3H 2 O mixed solution of Al(NO 3 ) 3 9H 2The concentration of the O solution is 0.1-0.5 mol / L, preferably 0.25 mol / L, Cu(NO 3 ) 2 ·3H 2 The concentration of the O solution is 0.3-1.5 mol / L, preferably 0.75 mol / L; the concentration of the NaOH solution is 0.5-3.0 mol / L; the pH is 9.0-10.0; the Na 2 CO 3 The concentration of the solution is 0.03-0.06 mol / L; the stirring time is 5-60 min, preferably 10-30 min.
[0011] Furthermore, in step (2), the concentration of the NaOH solution is 0.5-3.0 mol / L; the concentration of the rare earth nitrate solution is 0.05-0.80 mol / L, preferably 0.1-0.4 mol / L; the rare earth nitrate includes Sm(NO 3 ) 3 、Y(NO 3 ) 3 ,Gd(NO 3 ) 3 、Pr(NO 3 ) 3 hydrate; the pH is 9.0-10.0; the water bath temperature is 45-65°C, and the water bath time is 6-24h, preferably 8-15h.
[0012] Furthermore, in step (3), the calcination temperature is 300-600° C., and the calcination time is 1-6 hours, preferably 4 hours.
[0013] Furthermore, the Al(NO 3 ) 3 9H 2 O and Cu(NO 3 ) 2 ·3H 2 The sum of O and Na 2 CO 3 The molar ratio of Al(NO 3 ) 3 9H 2 O and Cu(NO 3 ) 2 ·3H 2 The molar ratio of the total amount of O to the rare earth nitrate is 1:0.025-0.4, preferably 1:0.05-0.3, and more preferably 1:0.05-0.15.
[0014] The present invention also provides a rare earth modified copper aluminum oxide catalyst prepared by the above preparation method.
[0015] The present invention also provides the use of the rare earth modified copper aluminum oxide catalyst in methanol steam reforming reaction.
[0016] Rare earth elements have unique 4f electronic structures and adjustable valence states. Rare earth oxides have abundant oxygen vacancies on their surfaces, so the use of rare earth modification methods can effectively construct active sites in copper-based catalysts (Cu + ) / Interface(Cu + / Cu 0 ) and modulate its catalytic activity. In addition, the dynamic transformation of the valence state of rare earth elements during the reaction is conducive to the dispersion of copper elements and thus improves the stability of copper-based catalysts in MSR reactions.
[0017] Further, the conditions of the methanol steam reforming reaction are: reaction space velocity of 30000-200000 mL / g / h, preferably 30000-120000 mL / g / h; reaction temperature of 200-300° C.; reaction atmosphere of 5-30 vol% CH 3 OH, 10-60 vol% H 2 O and balance gas N 2 The mixed gas is preferably 10 vol% CH 3 OH, 15 vol% H 2 O and balance gas N 2 of mixed gas.
[0018] Furthermore, the catalyst also includes an activation process, and the atmosphere of the activation process is 5-30 vol% H 2 and Ar, preferably 10 vol% H 2 and Ar mixed gas, the temperature of the activation process is 200-500°C, preferably 250-400°C, more preferably 300°C, the time is 0.5-4 hours, preferably 2 hours, and the pretreated catalyst is cooled to the target reaction temperature in a pure Ar atmosphere.
[0019] Furthermore, the catalyst is regenerated after the reaction, and the regeneration conditions are: treatment at 200-400°C for 0.5-4h, preferably 300°C for 1h in an air atmosphere, and then cooled to room temperature; the regenerated catalyst needs to be activated before reacting.
[0020] Furthermore, the catalyst after the reaction forms a coating structure in situ through the strong interaction between metal and support, and the coating structure is rare earth oxide coated copper nanoparticles.
[0021] The beneficial effects of the present invention are:
[0022] 1) The present invention develops a method for preparing a rare earth modified copper aluminum oxide catalyst based on rare earth modified copper aluminum hydrotalcite as a precursor. In the process of preparing hydrotalcite using a double drop method, the method directly introduces rare earth nitrate into the copper aluminum hydrotalcite to simply load the rare earth element on the copper aluminum hydrotalcite, and in the final rare earth modified copper aluminum oxide, no diffraction peak of rare earth oxide is observed by XRD, indicating that the rare earth element remains relatively well dispersed.
[0023] 2) The rare earth modified preparation strategy of copper aluminum hydrotalcite developed in the present invention effectively avoids the formation of copper oxide in the traditional copper aluminum hydrotalcite aging process, and the addition of rare earth elements promotes the formation of pure phase copper aluminum hydrotalcite. The rare earth modified copper aluminum oxide catalyst prepared by the present invention exhibits a strong metal-carrier interaction phenomenon in the methanol steam reforming reaction, forming an active structure of rare earth oxide-coated copper nanoparticles. The formation of the coating structure significantly improves the reaction activity of the copper aluminum oxide catalyst and significantly inhibits the agglomeration and sintering of copper nanoparticles, so that the rare earth modified copper aluminum oxide catalyst has good catalytic activity and stability in the methanol steam reforming reaction.
[0024] 3) The rare earth-modified copper-aluminum oxide catalyst prepared by the present invention exhibits better low-temperature activity in the methanol steam reforming reaction than the unmodified copper-aluminum oxide catalyst. 3 The OH conversion rate can reach 84.8%, and the catalytic activity of the unmodified copper-aluminum catalyst is increased by 30.6%. At the same time, the hydrogen production rate can reach 594.9mmol / g at a mass space velocity of 60000mL / g / h and a reaction temperature of 250℃. cat / h.
[0025] In addition, the rare earth modified copper aluminum oxide catalyst showed better stability than the unmodified copper aluminum oxide catalyst and the commercial copper zinc aluminum catalyst. The present invention establishes a regeneration method for the rare earth modified copper aluminum oxide catalyst. After the stability test, the catalyst is calcined in air at 300°C for 2h and then heated with 10% H 2 / Ar activation can restore the methanol steam reforming reaction activity of the rare earth modified copper aluminum oxide catalyst to its initial activity and maintain repeatable regeneration in multiple cycle tests. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a comparison chart of the activities of the rare earth modified copper aluminum oxide catalyst prepared in Example 1-4 and the copper aluminum oxide catalyst obtained in Comparative Example 1-2 in the methanol steam reforming reaction;
[0027] Figure 2 XRD spectra of the samarium-modified copper-aluminum hydrotalcite precursors prepared in Example 1 and Examples 5-6 and the copper-aluminum hydrotalcite obtained in Comparative Example 1;
[0028] Figure 3 a is a nitrogen adsorption-desorption curve diagram of the samarium-modified copper-aluminum oxide catalyst prepared in Example 1 and the copper-aluminum oxide catalyst obtained in Comparative Example 1, and b is a pore size distribution diagram of the samarium-modified copper-aluminum oxide catalyst prepared in Example 1 and the copper-aluminum oxide catalyst obtained in Comparative Example 1;
[0029] Figure 4 This is a comparison chart of the activities of the samarium-modified copper-aluminum oxide catalysts prepared in Example 1 and Examples 5-6 and the copper-aluminum oxide catalyst obtained in Comparative Example 1 in a methanol steam reforming reaction;
[0030] Figure 5 a is the samarium-modified copper aluminum oxide catalyst prepared in Example 6 in 10% H 2 a is a TEM image of the samarium-modified copper aluminum oxide catalyst prepared in Example 6 after being activated in an Ar atmosphere, b is a TEM image of the catalyst after being subjected to a methanol steam reforming reaction stability test, the stability test conditions being a reaction temperature of 250°C and a reaction space velocity of 60000 mL / g / h;
[0031] Figure 6 The stability test diagram of the samarium-modified copper aluminum oxide catalyst prepared in Example 6, the copper aluminum oxide catalyst obtained in Comparative Example 1, and the commercial copper zinc aluminum catalyst in Comparative Example 3 in the methanol steam reforming reaction, the reaction temperature is 250°C, and the reaction space velocity is 60000 mL / g / h;
[0032] Figure 7 The stability test diagram of the samarium-modified copper aluminum oxide catalyst prepared in Example 6 and the copper aluminum oxide catalyst obtained in Comparative Example 1 in the methanol steam reforming reaction, the reaction temperature is 300° C., and the reaction space velocity is 200000 mL / g / h;
[0033] Figure 8 a is the samarium-modified copper aluminum oxide catalyst prepared in Example 6 in 10% H 2 TEM image of the copper-aluminum oxide catalyst obtained in comparative example 1 after activation in 10% H / Ar atmosphere; b is the TEM image of the copper-aluminum oxide catalyst obtained in comparative example 1 after activation in 10% H 2 a is a TEM image of the samarium-modified copper-aluminum oxide catalyst prepared in Example 6 after being tested for stability in a methanol steam reforming reaction; and d is a TEM image of the copper-aluminum oxide catalyst obtained in Comparative Example 1 after being tested for stability in a methanol steam reforming reaction. The stability test conditions are a reaction temperature of 300°C and a reaction space velocity of 200,000 mL / g / h.
[0034] Fig. 9 These are the regeneration-stability test results of the samarium-modified copper aluminum oxide catalyst prepared in Example 6 in the methanol steam reforming reaction. DETAILED DESCRIPTION
[0035] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0036] The detailed preparation method of the catalyst provided by the present invention is as follows:
[0037] 1) Preparation of copper-aluminum hydrotalcite suspension: 0.1-0.5 mol / LAl(NO 3 ) 3 9H 2 O and 0.3-1.5mol / LCu(NO 3 ) 2 ·3H 2 O mixed solution and 0.5-3.0mol / LNaOH solution were added dropwise at a constant pH of 9.0-10.0 at the same time 2 CO 3 The solution is stirred for 5-60 minutes to obtain a copper-aluminum hydrotalcite suspension. Al(NO 3 ) 3 9H 2 O and Cu(NO 3 ) 2 ·3H 2 The sum of O and Na 2 CO 3 The molar ratio is 1-3:1.
[0038] 2) Preparation of rare earth modified copper aluminum hydrotalcite: 0.05-0.80 mol / L rare earth nitrate solution and 0.5-3.0 mol / L NaOH solution were dripped into the above suspension at a constant pH of 9.0-10.0, and aged in a water bath at 45-65°C for 6-24h to obtain rare earth modified copper aluminum hydrotalcite. Al(NO 3 ) 3 9H 2 O and Cu(NO 3 ) 2 ·3H 2 The molar ratio of the total amount of O to the rare earth nitrate is 1:0.025-0.4.
[0039] 3) Preparation of rare earth modified copper aluminum oxide: The rare earth modified copper aluminum hydrotalcite is calcined in air at 300-600° C. for 4 h to obtain a rare earth modified copper aluminum oxide catalyst.
[0040] The rare earth modified copper aluminum oxide catalyst was pretreated before the methanol steam reforming reaction. The process was as follows: 10% H 2 / Ar mixed gas, and heated to 200-500°C at a heating rate of 5°C / min, maintained for 2 hours, then cooled to the target reaction temperature in a pure Ar atmosphere, and then switched to the reaction gas for methanol steam reforming performance evaluation. Preferably, the conditions for the methanol steam reforming reaction are: reaction space velocity of 30000-200000mL / g / h; the reaction temperature of 200-300°C; the reaction atmosphere of 10% CH 3 OH, 15% H 2 O and balance gas N 2 .
[0041] The following examples and comparative examples are used to further illustrate the present invention, but are not intended to limit the present invention.
[0042] Example 1
[0043] Catalyst preparation
[0044] 1) Preparation of copper-aluminum hydrotalcite suspension: 0.25 mol / LAl(NO 3 ) 3 9H 2 O and 0.75mol / LCu(NO 3 ) 2 ·3H 2 O mixed solution 20mL and 1.5mol / LNaOH solution were added dropwise at a constant pH of 9.5, and 180mL of 0.056mol / LNa 2 CO 3 The solution was stirred for 20 min to obtain a copper-aluminum hydrotalcite suspension.
[0045] 2) Preparation of samarium-modified copper-aluminum hydrotalcite: 10 mL of 0.1 mol / L Sm(NO 3 ) 3 6H 2 O solution and 1.5 mol / L NaOH solution were dropped into the above suspension at a constant pH of 9.5, and aged in a 65° C. water bath for 12 h to obtain samarium-modified copper-aluminum hydrotalcite (denoted as 10Sm-CuAl-LDH).
[0046] 3) Preparation of samarium-modified copper aluminum oxide: The samarium-modified copper aluminum hydrotalcite was calcined in air at 500° C. for 4 h to obtain a samarium oxide-modified copper aluminum oxide catalyst (denoted as 10Sm-CuAl).
[0047] Catalyst activity evaluation
[0048] The methanol steam reforming reaction was carried out in a quartz tube fixed bed reactor with an inner diameter of 6 mm. The gas flow rates of each gas required for the experiment were adjusted and controlled by a mass flow meter and entered the reactor after being mixed evenly. 100 mg of 10Sm-CuAl was weighed into a quartz tube and first heated to 10% H 2 The reaction mixture was treated at 300 °C for 2 hours under a mixture of 10% CH 3 OH / 15%H 2 O / N 2 ; The reaction temperatures were 200℃, 220℃, 250℃, 270℃, and 300℃, respectively; the reaction space velocity was 30000mL / g / h; at 250℃, CH 3 The OH conversion rate can reach 84.8%. Figure 1 shown.
[0049] Example 2
[0050] The steps and process conditions for preparing the catalyst in this example are the same as those in Example 1, except that 10 mL of 0.1 mol / L Y(NO 3 ) 3 6H 2 O solution and 1.5 mol / L NaOH solution were dropped into the copper-aluminum hydrotalcite suspension at a constant pH of 9.5, and finally a yttrium oxide-modified copper-aluminum oxide catalyst (denoted as 10Y-CuAl) was obtained.
[0051] The methanol steam reforming reaction was carried out in a quartz tube fixed bed reactor with an inner diameter of 6 mm. The gas flow rates of each gas required for the experiment were adjusted and controlled by a mass flow meter and entered the reactor after being mixed evenly. 100 mg of 10Y-CuAl was weighed into a quartz tube and first heated to 10% H 2 The reaction mixture was treated at 300 °C for 2 hours under a mixture of 10% CH 3 OH / 15%H 2 O / N 2 ; The reaction temperatures were 200℃, 250℃, and 300℃ respectively; the reaction space velocity was 30000mL / g / h, and the results were as follows Figure 1 shown.
[0052] Example 3
[0053] The steps and process conditions for preparing the catalyst in this example are the same as those in Example 1, except that 10 mL of 0.1 mol / L Gd(NO 3 ) 3 6H2 O solution and 1.5 mol / L NaOH solution were dropped into the copper-aluminum hydrotalcite suspension at a constant pH of 9.5, and finally a gadolinium oxide-modified copper-aluminum oxide catalyst (denoted as 10Gd-CuAl) was obtained.
[0054] The catalyst activity test steps and process parameters are consistent with those described in Example 2. The results are as follows: Figure 1 shown.
[0055] Example 4
[0056] The steps and process conditions for preparing the catalyst in this example are the same as those in Example 1, except that 10 mL of 0.1 mol / L Pr(NO 3 ) 3 6H 2 O solution and 1.5 mol / L NaOH solution were dropped into the copper-aluminum hydrotalcite suspension at a constant pH of 9.5, and finally a praseodymium oxide-modified copper-aluminum oxide catalyst (denoted as 10Pr-CuAl) was obtained.
[0057] The catalyst activity test steps and process parameters are consistent with those described in Example 2. The results are as follows: Figure 1 shown.
[0058] Example 5
[0059] The steps and process conditions for preparing the catalyst in this example are the same as those in Example 1, except that 10 mL of 0.15 mol / L Sm(NO 3 ) 3 6H 2 O solution and 1.5 mol / L NaOH solution were dripped into the copper-aluminum hydrotalcite suspension at a constant pH of 9.5, and finally a samarium oxide-modified copper-aluminum oxide catalyst (denoted as 15Sm-CuAl) was obtained. 3 ) 3 6H 2 The concentrations of O solutions were 0.05 mol / L, 0.2 mol / L, and 0.7 mol / L, respectively. Using the same preparation method, 5Sm-CuAl, 20Sm-CuAl, and 70Sm-CuAl catalysts were obtained respectively.
[0060] The catalyst activity test steps and process parameters are consistent with those described in Example 2. The results are as follows: Figure 4 shown.
[0061] Example 6
[0062] The steps and process conditions for preparing the catalyst in this example are the same as those in Example 1, except that 10 mL of 0.3 mol / L Sm(NO 3 ) 3 6H 2 O solution and 1.5 mol / L NaOH solution were dropped into the copper-aluminum hydrotalcite suspension at a constant pH of 9.5, and finally a samarium oxide-modified copper-aluminum oxide catalyst (denoted as 30Sm-CuAl) was obtained.
[0063] The results of nitrogen physical adsorption and desorption tests showed that the catalyst had a 114 m 2 / g specific surface area.
[0064] The catalyst activity test steps and process parameters are consistent with those described in Example 2. The results are as follows: Figure 4 shown.
[0065] Catalyst stability test method
[0066] The stability test of methanol steam reforming reaction was carried out in a quartz tube fixed bed reactor with an inner diameter of 6 mm. The gas flow rates of each gas required for the experiment were adjusted and controlled by a mass flow meter and entered the reactor after being mixed evenly. 50 mg of 30Sm-CuAl was weighed into a quartz tube and first heated to 10% H 2 The reaction temperature was then lowered to the target reaction temperature and the stability test was performed under the following reaction conditions: the reaction atmosphere was 10% CH 3 OH / 15%H 2 O / N 2 The reaction temperature was 250℃ and 300℃, the reaction space velocity was 60000mL / g / h and 200000mL / g / h, and the results were as follows Figure 6 , Figure 7 shown.
[0067] Catalyst regeneration method
[0068] After the methanol steam reforming reaction stability test, anhydrous air was introduced into the 6 mm quartz tube fixed bed reactor and the temperature was raised to 300 °C at a heating rate of 5 °C / min for 1 h under anhydrous air atmosphere. The temperature was then lowered to room temperature and heated with 10% H 2 / Ar atmosphere at 300 °C for 2 h, then lowered to the target reaction temperature and heated to 10% CH 3 OH / 15%H 2 O / N 2 The methanol steam reforming reaction stability test was conducted again under the conditions of reaction temperature of 250°C and reaction space velocity of 60000mL / g / h. Fig. 9 shown.
[0069] Comparative Example 1
[0070] Catalyst preparation
[0071] 1) Preparation of copper-aluminum hydrotalcite: 0.25 mol / LAl(NO 3 ) 3 9H 2 O and 0.75mol / LCu(NO 3 ) 2 ·3H 2 O mixed solution and 1.5 mol / L NaOH solution were added dropwise at a constant pH of 9.5, and 180 mL of 0.056 mol / L NaOH solution was added dropwise. 2 CO 3 The solution was stirred for 20 min and aged in a 65° C. water bath for 12 h to obtain copper-aluminum hydrotalcite (denoted as CuAl-LDH).
[0072] 2) Preparation of copper aluminum oxide: The copper aluminum hydrotalcite prepared above was calcined in air at 500° C. for 4 h to obtain a copper aluminum oxide catalyst (denoted as CuAl).
[0073] Catalyst activity evaluation
[0074] The activity of methanol steam reforming reaction was evaluated under the reaction conditions described in Example 2 at a space velocity of 30000 mL / g / h. Under the conditions of 250°C, the CuAl catalyst CH 3 The OH conversion rate was 54.2%, as Figure 1 shown.
[0075] The catalyst stability test steps and process parameters are consistent with those described in Example 6. The results are as follows: Figure 6 , Figure 7 shown.
[0076] Comparative Example 2
[0077] 1) Preparation of samarium copper aluminum hydroxide by coprecipitation method: 0.25 mol / LAl(NO 3 ) 3 9H 2 O, 0.75 mol / LCu(NO 3 ) 2 ·3H 2 O and 0.05 mol / L Sm(NO 3 ) 3 40 mL of 1.2 mol / L NaOH solution was added dropwise to 20 mL of the mixed solution to obtain samarium copper aluminum hydroxide.
[0078] 2) Preparation of co-precipitated samarium copper aluminum oxide: The samarium copper aluminum hydroxide prepared above was calcined in air at 500° C. for 4 h to obtain a samarium copper aluminum oxide catalyst prepared by co-precipitation (denoted as 10SmCuAl-copre).
[0079] The catalyst activity test steps and process parameters are consistent with those described in Example 2. The results are as follows: Figure 1 shown.
[0080] Comparative Example 3
[0081] Commercial Cu / ZnO / Al 2 O 3 The catalyst was purchased from AlfaAesar.
[0082] The catalyst stability test steps and process parameters are consistent with those described in Example 6. The results are as follows: Figure 5 shown.
[0083] Combining Examples 1-6 and Comparative Examples 1-3, the activity comparison of the rare earth modified copper aluminum oxide catalyst prepared in Example 1-4 and the copper aluminum oxide catalyst obtained in Comparative Example 1-2 in the methanol steam reforming reaction is obtained. Figure 1 The XRD spectra of the samarium-modified copper-aluminum hydrotalcite prepared in Example 1 and Examples 5-6 and the copper-aluminum hydrotalcite obtained in Comparative Example 1 are shown as follows; Figure 2 As shown; the nitrogen adsorption and desorption test diagram and pore size distribution diagram of Example 1 and Comparative Example 1 are as shown Figure 3 The activity comparison of the samarium-modified copper-aluminum oxide catalyst prepared in Example 1 and Examples 5-6 and the copper-aluminum oxide catalyst obtained in Comparative Example 1 in the methanol steam reforming reaction is shown in FIG. Figure 4 As shown; TEM images of the samarium-modified copper-aluminum oxide catalyst prepared in Example 6 after activation and TEM images of the methanol steam reforming reaction stability test at 250°C are shown Figure 5 As shown; the stability test diagram of the samarium modified copper aluminum oxide catalyst prepared in Example 6, the copper aluminum oxide catalyst obtained in Comparative Example 1, and the commercial copper zinc aluminum catalyst in Comparative Example 3 in the methanol steam reforming reaction at a reaction temperature of 250°C and a reaction space velocity of 60000 mL / g / h is shown in Figure 6 As shown; the stability test diagram of the samarium modified copper aluminum oxide catalyst prepared in Example 6 and the copper aluminum oxide catalyst obtained in Comparative Example 1 in the methanol steam reforming reaction at a reaction temperature of 300°C and a reaction space velocity of 200000 mL / g / h is shown in Figure 7 The samarium-modified copper-aluminum oxide catalyst prepared in Example 6 and the copper-aluminum oxide catalyst obtained in Comparative Example 1 were treated with 10% H 2 TEM images after / Ar activation and TEM images after stability test under 300℃ and 200000mL / g / h reaction conditions are shown in Figure 8As shown; Example 6 Methanol steam reforming reaction regeneration - stability test results are as shown Fig. 9 As shown. From the above results, we can see that Figure 1 The results show that the rare earth modified copper aluminum oxide catalyst prepared with hydrotalcite as a precursor has a significantly improved catalytic activity in the low-temperature methanol steam reforming reaction compared with the unmodified copper aluminum oxide. At the same time, the activity of the samarium copper aluminum oxide catalyst 10Sm-CuAl prepared with hydrotalcite as a precursor is significantly better than that of the samarium copper aluminum oxide catalyst 10SmCuAl-copre prepared by the co-precipitation method, which proves that the use of copper aluminum hydrotalcite as a precursor can promote the good dispersion of copper elements. 10Sm-CuAl has a good performance in CH 3 The OH conversion rate can reach 84.8%, which is 30.6% higher than that of the unmodified copper-aluminum catalyst. Figure 2 It indicates that the rare earth modified copper-aluminum hydrotalcite prepared by the method of the present invention can effectively avoid the copper oxide appearing in the traditional copper-aluminum hydrotalcite preparation process and the added rare earth is evenly dispersed on the copper-aluminum hydrotalcite layer without obvious diffraction peaks. Figure 3 a in the figure shows that the specific surface area of samarium-modified copper-aluminum oxide is 114 m 2 / g, compared with unmodified copper aluminum oxide 57m 2 / g has a significant improvement, Figure 3 Figure b shows that the pore size distribution of the samarium-modified copper aluminum oxide catalyst is more concentrated than that of the unmodified copper aluminum oxide catalyst. Figure 4 It shows that the methanol steam reforming reaction activity of the samarium-modified copper-aluminum oxide catalyst prepared by the present invention using copper-aluminum hydrotalcite as a precursor is in a volcano curve relationship with the amount of samarium added. Figure 5 Figure a shows that 30Sm-CuAl in 10% H 2 / Ar activation after the presence of Sm 2 O 3 The lattice fringes are similar to those of Cu, but no characteristic Sm is seen in the TEM image. 2 O 3 Cu-coated structure. Figure 5 Figure b shows that Sm appeared in the TEM image of the 30Sm-CuAl catalyst after the stability test at 250℃ and 60000mL / g / h reaction space velocity. 2 O 3 The coated Cu nanoparticle structure indicates that a strong metal-support interaction occurs in the methanol steam reforming reaction to generate a coating structure in situ. The formation of the coating structure significantly improves the catalytic activity of the samarium-modified copper aluminum oxide catalyst in the methanol steam reforming reaction. Compared with the unmodified copper aluminum oxide catalyst and other rare earth element-modified copper aluminum oxide catalysts, the samarium-modified copper aluminum oxide catalyst has a significantly improved reaction activity at 250°C. Figure 6It shows that the hydrogen production rate of samarium-modified copper aluminum oxide catalyst 30Sm-CuAl at 250℃ can reach 594.9mmol / g at a space velocity of 60000mL / g / h cat / h. In the stability test at an air velocity of 60000mL / g / h, the absolute activity of the samarium-modified copper-aluminum catalyst decreased by 18.6% within 500min; compared with the 28.5% absolute activity decrease of the unmodified copper-aluminum oxide catalyst, it has a significant improvement. Compared with the 24.4% absolute activity decrease of the commercial copper-zinc-aluminum catalyst in the stability test, the samarium-modified copper-aluminum oxide catalyst is superior to the commercial copper-zinc-aluminum catalyst in terms of reaction activity and stability. Figure 7 It shows that under the reaction conditions of 300℃ and 200000mL / g / h, the unmodified copper aluminum oxide catalyst CuAl deactivated rapidly, indicating that under the conditions of high temperature and high space velocity, the Cu nanoparticles agglomerated, causing the catalyst structure to change, resulting in a rapid decrease in the activity of the methanol steam reforming reaction. The samarium-modified copper aluminum oxide catalyst 30Sm-CuAl deactivated more slowly than CuAl under the conditions of high temperature and high space velocity, and the deactivation rate was constant, indicating that the reason for its deactivation was that the intermediates in the methanol steam reforming reaction accumulated and slowly occupied the active sites, resulting in a decrease in catalyst activity. Figure 8 a and b show that 30Sm-CuAl and CuAl in 10% H 2 After / Ar reduction, the particle size distribution of Cu nanoparticles in the catalyst is relatively uniform and the particle sizes are similar. Figure 8 Figures c and d show that after the high-space-velocity and high-temperature stability test, the Cu nanoparticles in 30Sm-CuAl are still evenly dispersed and the particle size does not change significantly. The deactivation is caused by the accumulation of intermediates in the methanol steam reforming reaction. The obvious aggregation of Cu nanoparticles in the TEM image after the stability test of the CuAl catalyst indicates that the deactivation is caused by the agglomeration of Cu nanoparticles. 2 O 3 The coated Cu nanoparticle structure prevents the agglomeration of Cu under high temperature and high space velocity conditions. Fig. 9 The regeneration performance test shows that the samarium-modified copper-aluminum oxide catalyst prepared by the present invention has the ability to be repeatedly regenerated and the samarium-modified copper-aluminum oxide catalyst can be stably restored to its initial activity in multiple regeneration cycles. The intermediate adsorbed on the surface of the 30Sm-CuAl catalyst can be removed by air calcination, so that the catalyst can recover the methanol steam reforming activity after activation. 2 O 3The coated Cu nanoparticle structure hinders the agglomeration of Cu, so 30Sm-CuAl can be restored to its initial activity after air calcination to remove the accumulated intermediates. In summary, the rare earth modified copper aluminum oxide catalyst prepared by the present invention with copper aluminum hydrotalcite as the precursor has a strong metal-support interaction phenomenon in the methanol steam reforming reaction, and Sm is generated in situ. 2 O 3 The structure of the coated Cu nanoparticles. On the one hand, the formation of the coated structure significantly improves the methanol steam reforming reaction activity of the samarium-modified copper aluminum oxide catalyst. On the other hand, the coated structure hinders the agglomeration and sintering of copper nanoparticles during the reaction process, improves the stability of the catalyst and makes the catalyst regenerative.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing rare earth modified oxide using copper-aluminum hydrotalcite as a precursor, characterized in that: The following steps are involved: (1) A mixed solution of Al(NO3)3·9H2O and Cu(NO3)2·3H2O and a NaOH solution are simultaneously dropped into a Na2CO3 solution under a constant pH condition and stirred for a period of time to obtain a copper-aluminum hydrotalcite suspension; (2) adding a rare earth nitrate solution to the copper-aluminum hydrotalcite suspension obtained in step (1) and simultaneously dripping a NaOH solution to maintain a constant pH, and performing water bath aging to obtain a rare earth-modified copper-aluminum hydrotalcite; (3) calcining the rare earth-modified copper-aluminum hydrotalcite prepared in step (2) in air to obtain a rare earth-modified copper-aluminum oxide catalyst.
2. The preparation method according to claim 1, characterized in that: In step (1), the concentration of Al(NO3)3·9H2O solution in the mixed solution of Al(NO3)3·9H2O and Cu(NO3)2·3H2O is 0.1-0.5 mol / L, and the concentration of Cu(NO3)2·3H2O solution is 0.3-1.5 mol / L; the concentration of the NaOH solution is 0.5-3.0 mol / L; the pH is 9.0-10.0; the concentration of the Na2CO3 solution is 0.03-0.06 mol / L; and the stirring time is 5-60 min.
3. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the NaOH solution is 0.5-3.0 mol / L; the concentration of the rare earth nitrate solution is 0.05-0.80 mol / L; the rare earth nitrate includes hydrates of Sm(NO3)3, Y(NO3)3, Gd(NO3)3, and Pr(NO3)3; the pH is 9.0-10.0; the water bath temperature is 45-65°C, and the water bath time is 6-24h; in step (3), the calcination temperature is 300-600°C, and the calcination time is 1-6h.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the sum of Al(NO3)3·9H2O and Cu(NO3)2·3H2O to Na2CO3 is 1-3:1; the molar ratio of the sum of Al(NO3)3·9H2O and Cu(NO3)2·3H2O to rare earth nitrate is 1:0.025-0.
4.
5. A rare earth modified copper aluminum oxide catalyst prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the rare earth-modified copper-aluminum oxide catalyst according to claim 5 in methanol steam reforming reaction.
7. The use according to claim 6, characterized in that: The conditions of the methanol steam reforming reaction are: reaction space velocity of 30000-200000 mL / g / h; reaction temperature of 200-300° C.; reaction atmosphere of a mixture of 5-30 vol% CH3OH, 10-60 vol% H2O and N2.
8. The use according to claim 6, characterized in that: The catalyst also includes an activation process, the activation atmosphere is a mixed gas of 5-30 vol% H2 and Ar, the activation temperature is 200-500°C, and the activation time is 0.5-4 hours.
9. The use according to claim 6, characterized in that: After the reaction, the catalyst is regenerated under the following conditions: treatment at 200-400°C for 0.5-4 hours in an air atmosphere; the regenerated catalyst also needs to be activated.
10. The use according to claim 6, characterized in that: The catalyst after the reaction forms a coating structure in situ through the strong interaction between the metal and the carrier, and the coating structure is the copper nanoparticles coated with rare earth oxides.
Citation Information
Patent Citations
Modified Cu-Al hydrotalcite catalyst for hydrogen chloride oxidation and preparation method and application of modified Cu-Al hydrotalcite catalyst
CN111450881A
Preparation method of copper-based catalyst with copper-coated zinc oxide interface and application of copper-based catalyst in low-temperature catalysis of water gas shift reaction
CN114824320A
Preparation method of copper-based rare earth catalyst for hydrogen production by methanol steam reforming
CN116173971A
Nano carbon material modified copper base catalyst and its preparing method
CN1586718A
Catalyst precursor for methanol steam reforming, catalyst for methanol steam reforming and its manufacturing method
JP2002079101A